Effects of Microfinance Services on Economic Status Improvement: A Case of SKBBL, Pokhara, Nepal - Dhungana, Bharat Ram; Timlasina, Arjun; Thapa, Bandana; Tiwari, Devi Raman Tiwari (Quest Journal of Management and Social Sciences, 2022)
Background: Microfinance is an effective tool for financial inclusion and poverty reduction in developing countries like Nepal. It delivers financial and non-financial services to unbanked people from formal financial services. Microfinance services support people from weaker sections of society with a view of socio-economic transformation. Low access to finance is a problem for poor and marginalized people. Microfinance institutions provide microcredit to unbanked people without physical collateral. Thus they help people from lower-income groups improve their livelihood through productive investment. Objectives: This paper aims to examine the effects of microfinance services on the economic status of clients' status with references to Sana Kisan Bikas Laghubitta Bittiya Sanstha Limited (SKBBL), Pokhara, Nepal. Methods: The research presents the findings of data collected through a survey research design in the Kaski district of Nepal. The researchers administered the survey questionnaire to 235 clients of SKBBL microfinance institutions involved in the programme for the last five or more years. We used a stratified random sampling technique to collect the data. The sample population comprised 70 from a scheduled caste (Dalit), 75 from ethnic groups, and 90 from upper castes. Both descriptive and inferential statistics have been used to analyze the data. The paired sample t-test has been used to examine the effects of microfinance intervention on occupational status, income level, consumption expenditure, capital expenditure, and monthly savings of the clients. Results: The results show that microfinance has contributed a significant role. It has enabled people from lower income groups to access microcredit and encourage productive investment that facilitates productive investment and economic transformation. -The result derived from paired sample t-test finds the positive effects of microfinance intervention on occupational status, income level, consumption, capital expenditure, and saving habits. Conclusion: This study concludes that role of microcredit is significant in enhancing the clients' economic status. Microfinance positively affects clients' earnings, savings, spending, asset accumulation, and occupational status. However, utilizing microcredit in productive sectors is necessary to empower the clients' economic status. The findings indicate that microfinance institutions must focus on effective microcredit applications to help create micro-businesses and improve the clients' livelihood status.